Mechanism of Action and Clinical Efficacy of CDK4/6 Inhibitors in BRCA-Mutated, Estrogen Receptor-Positive Breast Cancers: Case Report and Literature Review - Militello, Anna Maria; Zielli, Teresa; Boggiani, Daniela; Michiara, Maria; Naldi, Nadia; Bortesi, Beatrice; Zanelli, Paola; Uliana, Vera; Giuliotti, Sara; Musolino, Antonino (Frontiers in Oncology, 2019)
Sensitivity to endocrine therapy of patients with estrogen receptor (ER)-positive metastatic breast cancer and germline BRCA1/2 mutations is not yet fully elucidated. Furthermore, the registration trials of CDK 4/6 inhibitors in combination with endocrine therapy lacked of a pre-specified subgroup analysis in BRCA1/2 mutation carriers. We report clinical history of two patients with BRCA-mutated, ER-positive metastatic breast cancer treated with letrozole plus the CDK 4/6 inhibitor palbociclib. Biological and clinical implications of the treatment outcome observed in the two cases are discussed with the knowledge of scientific evidence to date available. Overall, biological rationale, preclinical and clinical data support the prominent role of CDK 4/6 inhibitors plus endocrine therapy, even in combination with PARP inhibitors, in the treatment of BRCA-mutated, ER-positive breast cancers. However, the interaction between Cyclin/CDK pathway, ER and BRCA is complex and evidences reported so far, albeit reliable, await confirmation in the context of future randomized clinical trials.